THE STRUGGLE FOR SOCIAL WELFARE: TOWARDS AN EMERGING WELFARE SOCIOLOGY - BARANOWSKI, MARIUSZ (Society Register, 2019)
The main aim of the article is to outline welfare sociology as a potential sub-discipline of sociology and to discuss the issues of broadly defined social welfare. While in contemporary social sciences the literature concerning welfare often focuses on themes such as happiness (psychology), prosperity (economics), or quality of life (sociology), these themes may be considered too narrow and do not reflect the complexity of the issue. However, if one considers the definition of social welfare through the prism of material and non-material needs, as well as the needs expressed individually and collectively, it is possible to attempt a comprehensive study of this phenomenon. The author uses the definition of social welfare to look at research on (a) welfare state regimes, (b) welfare attitudes and (c) issues of work in contemporary capitalism, all to enable the application of research results within the analysis of the title concept.